Emerging in vitro models to study Merkel cell carcinoma pathobiology - Mazziotta, Chiara; Rotondo, John Charles (Frontiers in Cell and Developmental Biology, 2025)
Merkel cell carcinoma (MCC) is a rare but highly aggressive skin neoplasm, caused in approximately 80% of cases by the genomic integration of Merkel cell polyomavirus (MCPyV) and the expression of the viral small T antigen (sT) and large T antigen (LT) oncoproteins. Virus-negative tumors exhibit extensive UV-induced mutations. Despite such divergent molecular characteristics, the two etiologies share similar morphological and clinical features. The development of novel preclinical in vitro models that effectively recapitulate MCC pathobiology is essential for understanding the mechanisms of MCPyV infection and the cellular ancestry of MCC, a central topic of ongoing investigation and debate. This review provides a comprehensive overview of current two-dimensional (2D) and three-dimensional (3D) in vitro models developed to investigate the molecular and cellular mechanisms of MCC onset and progression. Continuous refinement of cell models that recapitulate MCC pathobiology is essential for advancing our understanding of the mechanisms of tumor onset and progression, thereby enhancing clinical applications for MCC patients.